Energy flows with intentional changes in leg movements during baseball pitching - Matsuda, Ryota; Hirano, Yuichi; Umakoshi, Jun; Kimura, Arata (Frontiers in Sports and Active Living, 2025)
Baseball pitchers are typically required to generate high ball velocity in their pitches. Many studies have focused on the lower extremity movements engaged at the beginning of the pitching motion to generate high ball velocity. It is assumed that the change in movement of the lower extremity induces the change in energy flow in pitching because the lower extremity generates high mechanical energy transferred to the ball. However, no studies have focused on the effects of intentional changes in lower extremity movements on energy flow. This study examined how altering stride length changes the energy flow from the lower extremities to the trunk. Twenty male college baseball pitchers participated in this study. In addition to pitching with normal stride length (NS), they pitched with under-stride length (US) and over-stride length (OS), defined as ±20% of NS. The positive and negative work of joint power, the sum of joint force power and segment torque power, were analyzed at the pivot hip, stride hip, and trunk joint. Positive work was defined as energy inflow to the lower torso from each joint, while negative work was defined as energy outflow from the lower torso to each joint. These values were then compared across stride length conditions. Our results showed that the energy inflow from the pivot hip to the lower torso and outflow from the lower torso to the stride hip changed with stride length during each phase. However, the total energy outflow from the lower torso to the trunk joint during the stride and arm-cocking phase was not significantly different with stride length (p = 0.59; η2 = 0.02), and the ball velocity did not significantly differ between the US and OS (p = 1.00; d < 0.01). This study highlights that altering stride length might not lead to changes in total energy outflow from the lower torso to the trunk joint, implying difficulties in explaining ball velocity only by the lower extremity mechanics.